THE CARE RELATIONSHIPIN THE TEST OF ARTIFICIAL INTELLIGENCE: BREAK OR CONTINUITY? - QUESNE, Aloïse (MEDECINE LEGALE DROIT MEDICAL, 2025)
The study of the care relationship invites an analysis of the basic principles that govern it. Some principles, shaken by the development of artificial intelligence, are forced to adapt, while new principles will have to appear. The revolution is not and must not be complete in this matter, but artificial intelligence necessarily upsets the relationship of care. We are therefore witnessing a search for a balance between the role of the doctor and that of artificial intelligence, but also with regard to the rights and duties of the patient in the presence of artificial intelligence, the new actor in the care relationship.